Intolerance to and limitations of inspiratory muscle training in patients with advanced chronic obstructive pulmonary disease: A report of two cases. (2020) - Yamamoto, Yuji; Miki, Keisuke; Matsuki, Takanori; Fukushima, Kiyoharu; Oshitani, Yohei; Kagawa, Hiroyuki; Tsujino, Kazuyuki; Yoshimura, Kenji; Miki, Mari; Kida, Hiroshi
Abstract: Inspiratory muscle training (IMT) has been attracting attention as one of the useful treatments in patients with chronic obstructive pulmonary disease (COPD). IMT is reportedly effective in most patients with COPD. However, little is known about the benefits of IMT, especially in patients with advanced COPD. We reported two cases of COPD that received 12-week IMT to explore intolerance to and the limitations of IMT in advanced COPD. The effectiveness of IMT was evaluated using cardiopulmonary exercise testing (CPET), spirometry, and respiratory muscle strength testing before and after the training. A 75-year-old man with normal body mass index (BMI) and forced expiratory volume in 1 s (FEV1 ) of 1.63 L responded well to IMT, but a 78-year-old man with low BMI and FEV1 of 0.83 L did not. In the responder, IMT resulted in increased minute ventilation ( V' E ) and oxygen uptake at peak exercise in incremental load testing. Moreover, IMT increased endurance time in constant load testing and maximal inspiratory pressure. In both patients, breathing frequency ( f R ) increased, but tidal volume and the inspiratory-expiratory ratio were not improved during exercise. Despite the high f R obtained after IMT, V' E at peak exercise did not increase and endurance time shortened in the non-responder. In underweight patients with advanced COPD, IMT might lead to tachypnea and ventilatory inefficiency, which in turn might decrease exercise performance. Therefore, underweight patients with advanced COPD might be unable to tolerate IMT and should avoid receiving the training.